Kiswahili na utaifa nchini Kenya - Momanyi, Clara; Njogu, Kimani; Mukuthuria, Mwenda (Nairobi, Kenya : Twaweza Communications, 2012)
On the Swahili language and nationalism in Kenya.
Includes bibliographical references.
Keywords: Swahili language -- Political aspects -- Kenya; Nationalism -- Kenya; Language policy -- Kenya